EFFECT OF SEX ON Toxocara canis LARVAL MIGRATION TO THE CEREBELLUM DURING EXPERIMENTAL INFECTION OF Rattus norvegicus - Henrique Yazawa dos Santos, Felipe; Paulo Chieffi, Pedro; Angelica Zevallos Lescano, Susana; Rodrigues e Fonseca, Gabriela; Vieira dos Santos, Sergio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
The presence of Toxocara canis third instar larvae in the cerebellum of Rattus norvegicus may alter rodent behavior and movement. In this study, we investigated whether the sex of the rodent affects the migration of larvae to the cerebellum. Thirty-six Rattus norvegicus specimens (18 males and 18 females) were infected with 300 T. canis eggs and were euthanized after 60 days. The cerebellum was removed and treated with 0.5% HCl to recover the T. canis larvae. The number of larvae recovered from male rodents was significantly higher than in females, suggesting that the sex of the animal influences larval migration to the cerebellum.